PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN KONSUMEN DI PT REXVIN PUTRA MANDIRI - Siswati, Yelna; Evyanto, Winda (SCIENTIA JOURNAL, 2021)
The Purpose of this research is to identify the effect of product quality and promotion to customer satisfaction at PT Rexvin Putra Mandiri. The research was using simple random sampling to obtain the sample from the total consumers of the Prasetya Residence project. The research data were obtained from a questionnaire distributed to 104 consumer respondents in the Prasetya Residence project. Using descriptive analysis to analyze the collected data from sample. The research method used is quantitative causality. Test data quality using validity and reliability tests. The classic assumption tests are using normality, multicollinearity, and heteroscedasticity tests. Multiple linear regresion analysis and coefficient of determination for influence test. Hypothesis testing using the t test (partially) and F test (simultaneously). The results showed that t count of product quality variables and t count of promotional variables was more than than t table and the significance was under 0.05. And F value is more than than the F table and the significance is under 0.05. So it can be stated that partially, the customer satisfaction is affected significant and positive by variable product quality and promotion. Customer satisfaction was simultaneously affected significant and positive by the variables of product quality and promotion together.